Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1021/bi980385m
|View full text |Cite
|
Sign up to set email alerts
|

Chain Length and Temperature Dependence of the Reversible Association of Model Acylated Proteins with Lipid Bilayers

Abstract: To study the binding of fatty-acylated proteins to lipid bilayers, we have specifically attached fatty acids to the N-terminus of chemically modified bovine pancreatic trypsin inhibitor. This was accomplished by reacting the protein with saturated fatty acid anhydrides ranging in length from 8 to 18 carbons. Following radiolabeling of the fatty-acylated proteins at Lys-15, binding of these proteins to palmitoyloleoyl phosphatidylcholine vesicles was examined as a function of temperature using ultracentrifugati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 45 publications
3
48
1
Order By: Relevance
“…Studies involving phospholipid bilayers have nevertheless suggested that single lipid modification does not stably anchor proteins in membranes but rather acts as a facilitator of the interaction (Peitzsch and McLaughlin, 1993;Pool and Thompson, 1998). The strength of the interaction appears to depend on the length of the fatty acid chain (PAL > MYR).…”
Section: Proteins Displaying Only An N-terminal Myred Site: the Plantmentioning
confidence: 99%
“…Studies involving phospholipid bilayers have nevertheless suggested that single lipid modification does not stably anchor proteins in membranes but rather acts as a facilitator of the interaction (Peitzsch and McLaughlin, 1993;Pool and Thompson, 1998). The strength of the interaction appears to depend on the length of the fatty acid chain (PAL > MYR).…”
Section: Proteins Displaying Only An N-terminal Myred Site: the Plantmentioning
confidence: 99%
“…It is well established that attachment of a single myristoyl group to a soluble protein only marginally affects its partitioning affinity for nonpolar (membrane) surfaces [87,88]. Generally, a second acylation event involving palmitate (16 carbons) is needed for soluble proteins to form strong, stable associations with membranes.…”
Section: Gltp Conformational Structurementioning
confidence: 99%
“…Membrane binding of such lipid-modified proteins is primarily driven by the hydrophobic effect; that is, dehydration of the lipid moiety upon membrane insertion gives rise to a large, favorable change in Gibbs free energy. Hydrophobic burial of an aliphatic chain is accompanied by a change in Gibbs free energy of À3.45 kJ/mol per methylene group (4,5), thus providing a strong driving force for membrane binding of proteins and peptides bearing longchain lipid modifications. However, hydrophobicity is not the only factor at play, because membrane binding is further modulated by electrostatic interactions (most notably, Coulombic attraction to or repulsion from the membrane and polar (de)hydration effects) as well as an entropic penalty incurred when an intrinsically flexible macromolecule binds to a membrane (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic burial of an aliphatic chain is accompanied by a change in Gibbs free energy of À3.45 kJ/mol per methylene group (4,5), thus providing a strong driving force for membrane binding of proteins and peptides bearing longchain lipid modifications. However, hydrophobicity is not the only factor at play, because membrane binding is further modulated by electrostatic interactions (most notably, Coulombic attraction to or repulsion from the membrane and polar (de)hydration effects) as well as an entropic penalty incurred when an intrinsically flexible macromolecule binds to a membrane (4)(5)(6)(7). From detailed quantitative thermodynamic analyses of several such interactions (4,8), it has been concluded that at least two lipid modifications are required to tightly anchor a protein to a lipid bilayer membrane such as to reduce the fraction of free protein in the aqueous phase to negligible values (2).…”
Section: Introductionmentioning
confidence: 99%